Emotional Mental Health Among Adolescents: A Profiling Psychosocial Risk Distribution - Emma Aprilia Hastuti; Vena Annisa Rudianty; Ade Iwan Mutiudin; Deris Riandi Setiawan (STIKep PPNI Jawa Barat, 2026)
Background: Adolescents are a vulnerable population to emotional and mental health problems due to rapid biological, psychological, and social changes. National surveys have reported increasing levels of anxiety, loneliness, and behavioral problems among adolescents; however, local evidence describing the distribution of adolescent emotional and mental health problems remains limited, particularly in school settings. Objective: This study aimed to describe the distribution and profile of emotional and mental health problems among adolescents based on school-based psychosocial screening in Bandung Regency, Indonesia. Methods: A descriptive quantitative study with a cross-sectional design was conducted involving 1,304 adolescents who participated in a school-based mental health screening program in 2025. Emotional and behavioral problems were assessed using the Strengths and Difficulties Questionnaire (SDQ), covering five domains: emotional symptoms, conduct problems, hyperactivity, peer relationship problems, and prosocial behavior. Data were analyzed descriptively using frequencies and percentages. Results: Most adolescents were classified as normal in the domains of emotional symptoms (67.9%), conduct problems (67.2%), hyperactivity (81.8%), and prosocial behavior (57.8%). However, a relatively high proportion of abnormal scores was observed in peer relationship problems (27.1%) and emotional symptoms (20.6%). Based on the total difficulties score, 3.4% of adolescents were categorized as abnormal, indicating the presence of a psychosocial risk burden within the adolescent population. These findings suggest that peer relationship difficulties and emotional problems constitute prominent areas of concern. Conclusion: This study provides a descriptive overview of emotional and mental health problems among adolescents identified through school-based psychosocial screening. The findings underscore the potential role of routine screening in supporting early identification of adolescents at risk of psychosocial difficulties. Further evaluative and longitudinal studies are needed to assess the effectiveness of screening programs and related interventions in improving adolescent mental health outcomes